2022
DOI: 10.3390/plants11202796
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review on the Main Flavonoids Found in Some Species of the Myrtaceae Family: Phytochemical Characterization, Health Benefits and Development of Products

Abstract: This integrative review aims to identify the main flavonoids present in some species of the Myrtaceae family. Studies published between 2016 and 2022 were selected, specifically those which were fully available and written in Portuguese, English, or Spanish, and which were related to the fruits araçá (Psidium cattleianum), cambuí (Myrciaria floribunda), gabiroba (Campomanesia xanthocarpa), jabuticaba (Plinia cauliflora), and jambolan (Syzygium cumini). Scientific studies were gathered and selected in Google Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…The results obtained from the present work are in agreement with the data from others studies which show that local plants could improve the regulation of the molecular mechanisms involved in diabetes control due to their bioactive compounds [ 14 , 21 ]. Polyphenols and flavonoids are especially evident in antioxidant, anti-inflammatory, antimicrobial, antihypertension, and antidiabetic processes in the human body [ 22 , 23 , 24 ]. These findings support the results of our recent survey, which showed that the local population in Mali uses the fruits of these two species for the traditional treatment of hypertension [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained from the present work are in agreement with the data from others studies which show that local plants could improve the regulation of the molecular mechanisms involved in diabetes control due to their bioactive compounds [ 14 , 21 ]. Polyphenols and flavonoids are especially evident in antioxidant, anti-inflammatory, antimicrobial, antihypertension, and antidiabetic processes in the human body [ 22 , 23 , 24 ]. These findings support the results of our recent survey, which showed that the local population in Mali uses the fruits of these two species for the traditional treatment of hypertension [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…These data are in line with those of Azarpazhooh et al [ 32 ] who registered significantly higher contents of anthocyanins (from 59.7 to 73.1 mg GA/kg) by increasing the percentage of maltodextrin from 5 to 15%. The literature showed the involvement of a number of bioactive compounds, especially flavonoids and polyphenols, in DPPH and ABTS radical scavenging from plant extracts and food [ 24 , 32 ]. Moreover, the highest antioxidant effect was obtained from ABTS radical scavenging for Z. mauritiana with 86.81 ± 1.47 µM TE/g and from DPPH radical scavenging for B. aegyptiaca with 17.87 ± 1.77 µM TE/g.…”
Section: Resultsmentioning
confidence: 99%
“…There were prominent peaks in the region 1307–1025 cm −1 . Here, the presence of ether, esters, and carboxylic acids, are indicative of a wide range of metabolites, including tannins, flavonoids and anthraquinones, among others 50 .
Figure 1 Comparison of FT-IR spectrum of guggul stored in Eathen pots.
…”
Section: Resultsmentioning
confidence: 99%
“…Qiu (Qiu et al, 2021) measured the volatile components of jaboticaba at different developmental stages via headspacegas chromatography/mass spectrometry and found the most predominant volatile components were monoterpenes, including a-pinene, b-pinene, and D-limonene. Jaboticaba is also considered as an edible health benefits plant and its pulp is rich in acids, sugars, vitamins, dietary fiber, minerals, and polyphenols (Qiu et al, 2021;Correia et al, 2022;Boldori et al, 2023). There are numerous phenolic substances, including anthocyanins, ellagic acid, and tannins (Pereira et al, 2017;Albuquerque et al, 2020;Fernandes et al, 2020) in the peel, which afford various biological activities, such as antioxidation, anti-inflammatory, antibacterial, hypoglycemic, and lipid-lowering properties (Inada et al, 2018;Zhao et al, 2019;Ferreira et al, 2021;Geraldi et al, 2021;Da Silva-Maia et al, 2023).…”
Section: Discussionmentioning
confidence: 99%